The procession of Hoyak Tabuik: a tourism urgency and education values in Pariaman City - Nanda Nelri (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2018)
This article is purposed to inform the performance analysis of Hoyak Tabuik procession in Pariaman community. Hoyak Tabuik is a cultural legacy in Pariaman community, which is performed annually in Pariaman City. Recently, Hoyak Tabuik ritual procession has been a tourism interest for Pariaman goverment. In addition to cultural legacy, Hoyak Tabuik ritual also a performance that attracting tourists, either domestic or foreign tourists, to visit Pariaman as tourism object. Hoyak Tabuik procession is also has educational values in cultural aspect. Therefore, Hoyak Tabuik ritual procession is important for community and government in Pariaman City at this moment.